The Study of Effective Communication to Overcome Design Change in Construction Project - Mayudi, Nurul Nasirah; Khalid, Zailawati; Sarpin, Norliana (Research in Management of Technology and Business, 2022)
Effective communication in construction industry is a core competency element to the success of the project. Communication becomes a huge problem and a major component in defining events in the construction industry as the industry becomes more complicated and the industry organization becomes thinner. Ineffective communication leads to insufficient instruction, which might cause work to be completed in the incorrect order. The issues that arise in the construction industry are due to a lack of communication. One of the repercussions of ineffective communication on construction projects is the occurrence of rework and redesign. Reworks and design changes are frequently carried out during the project lifecycle as a result of inadequate communication, resulting in time and expense overruns. Therefore, the objective of this study is to identify the consequence of ineffective communication in design change in construction project and to determine the effective communication to overcome design change in construction project. The approach of this study is using qualitative method by interview of three contractors and three architects who were working in Selangor. Primary data was obtained through a qualitative approach to collect complete information related to the objectives of the study. Data analysis procedure for the interview result was analyzed by using thematic analysis method. The finding of this study revealed the consequences of ineffective communication towards design change are cost overruns, time overruns, rework and high accident rate. Therefore, by effective communication can overcome design change in construction by improving communication through innovation, by using 3D project model, Virtual Reality (VR) and by using Building Information Modelling (BIM).